Flexibility in usability versus infection control: study of selected primary care clinics in Malaysia for future design decisions - Mohd Nawawi, Norwina; Md Alwi, Nadiah; Wan Nor, Wan Fatihah Maisarah; Md Alwi, Ahmad Naufal; Shafiei, Rahawiah (2018)
Primary care clinics are the first port of call for all ailments except for the Emergency Department or Unit, in any healthcare facilities. Until the patients are diagnosed, infections are bound to occur. Many of the primary care clinic building designs in Malaysia are ranged from those built during the colonial days in 18th Century to current. Many designs had evolved to meet both the demand for capacity, the types of ailments and services in the urban and rural areas. With high mobility and migration of people in the region due to circumstances of war, technology and economics, statistics shows old and new infectious diseases are on the rise. The design of these clinics as the first bastion to prevent further cross-infection is therefore questionable. From the selected clinic design as case studies, this paper described qualitatively, through exploration and deduction from secondary and primary data, the extent of versatility or flexibility from architectural design aspects, how each layout, from exterior to interior, are able or unable to withstand the consequence of cross-infection. Apart from the influence of the physical layout of the clinics in terms of space planning, ventilation, circulation and orientation; findings had indicated that self-discipline and behaviour of the users (staff, patients and accompanying relatives/friends) also need to observe infection control whenever they are in the clinic to prevent infection. Flexibility in clinic design should not only address the clinical needs in its standard operating procedure (sop) but also to address the distinct human behaviour and culture of the demography of the region. Only then perhaps, the design decisions made would address the paramount concerns of cross-infection in design succinctly.